Myocardial afterload regulates atrioventricular valve development in zebrafish - Ahuja, Neha, author; Garrity, Deborah, advisor; Sloan, Daniel, committee member; Mykles, Don, committee member; Tjalkens, Ron, committee member (Colorado State University. Libraries, 2020)
The incidence of congenital heart disease (CHD) is estimated to be 1% of all human births. CHD of the heart valves occurs in over 50% of CHD cases. Despite significant clinical interest, the molecular mechanisms that govern valve development remain poorly elucidated. As the heart develops, blood flow and blood pressure increase rapidly to support the growing demands of the embryo. Our group has previously shown that pressure at the developing atrioventricular valve dramatically increases through development. Consequently, we hypothesized that afterload—defined as the pressure the ventricle must overcome in order to pump blood through the body—may be a cue that cardiac valve cells read and respond to build a valve leaflet. Here, we present a zebrafish model in which afterload has been increased through the use of vasopressin, a vasoconstrictive drug. We first show that application of vasopressin reliably produces an increase in afterload without directly acting on cardiac tissue in zebrafish embryos. To evaluate cardiac function and valve leaflet dynamics, we took a quantitative live-imaging approach. Consistent with pathology seen in adult human patients with clinically high afterload, we see defects in both form and function of the valve leaflets. To identify the cause of this functional defect, we utilized in situ hybridization to evaluate makers of cell differentiation for both valve leaflet cells and the adjacent myocardial cells. Our results suggest that this valve defect is due to changes in atrioventricular myocyte differentiation and signaling, rather than pressure directly acting on the valve leaflet cells. We next took a transcriptomics approach to identify regulators of atrioventricular myocyte differentiation and identified a subset of differentially expressed transcription factors that are putatively responsible for sensing afterload. Together, our results show that afterload regulates the physiological and molecular state of the developing valve.
Keywords: developmental biology; valve; biomechanics; zebrafish; heart